Strategi Pemberdayaan Petani Pala Dalam Meningkatkan Kualitas Tanaman Pala Oleh Dinas Perkebunan Di Kabupaten Fakfak - Misrull Ashary Naisin; Muhammad Fandy Asyik (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2022)
Fakfak Regency is the largest producer of nutmeg in West Papua Province and has been very famous since ancient times. However, in fact, the quantity of nutmeg produced is not directly proportional to the quality produced. Therefore, the selling value of nutmeg from Fakfak Regency is low in the market so that it is difficult for nutmeg farmers to achieve prosperity. The purpose of this paper is to find out how the community empowerment strategy of nutmeg farmers in improving the quality of nutmeg crop yields in Fakfak Regency is carried out by the Department of Plantation of Fakfak Regency and also to determine the supporting factors and resisting factors. The author gives advice to all parties, especially to the Plantation Office of Fakfak Regency to continue to preserve the forest as a habitat for nutmeg plants and be consistent in carrying out planned programs and take advantage of the times to help promotion and market nutmeg online because it will be very effective and efficient for now and in the future.